2022
DOI: 10.15252/embj.2021109365
|View full text |Cite
|
Sign up to set email alerts
|

Airway secretory cell fate conversion via YAP‐mTORC1‐dependent essential amino acid metabolism

Abstract: Tissue homeostasis requires lineage fidelity of stem cells. Dysregulation of cell fate specification and differentiation leads to various diseases, yet the cellular and molecular mechanisms governing these processes remain elusive. We demonstrate that YAP/TAZ activation reprograms airway secretory cells, which subsequently lose their cellular identity and acquire squamous alveolar type 1 (AT1) fate in the lung. This cell fate conversion is mediated via distinctive transitional cell states of damage-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For instance, ATF4 is an important regulator of metabolic reprogramming in myofibroblasts [ 29 ]. In fact, TRIB3 is a target of CHOP/ATF4; when up-regulating ATF4 expression, the level of TRIB3 was markedly increased [ 16 , 34 ]. Several studies have shown that TRIB3 interacts with ATF4 and inhibits ATF4 transcription activity [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ATF4 is an important regulator of metabolic reprogramming in myofibroblasts [ 29 ]. In fact, TRIB3 is a target of CHOP/ATF4; when up-regulating ATF4 expression, the level of TRIB3 was markedly increased [ 16 , 34 ]. Several studies have shown that TRIB3 interacts with ATF4 and inhibits ATF4 transcription activity [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…FAK stimulates PI3K/Akt signaling, whereas PI3K/Akt activation increases the levels of glutamine and its synthetase ( Van Der Vos et al, 2012 ). The YAP/TAZ pathway plays an important role in amino acid metabolic reprogramming ( Jeon et al, 2022 ), and FAK/Src signaling has been shown to mediate the activation of YAP/TAZ signaling in tumor cells ( Totaro et al, 2018 ; Ma et al, 2020 ). However, there are still questions regarding the specific mechanisms of FAK in amino acid metabolic reprogramming, such as whether it affects the expression of key enzymes and whether there are key signaling pathways.…”
Section: Mechanism By Which Focal Adhesion Kinase Regulates Tumor Pro...mentioning
confidence: 99%
“…In mouse lungs, continuous activation of YAP/TAZ induces the mTOR-ATF4 signaling pathway and leads to changes in the cell fate and identity of secretory airway cells and their conversion into squamous AT1-like cells [ 102 ]. In human bronchial epithelial cells (HBEC3s) an active interaction was found between YAP and mTOR/PI3K/AKT pathway, resulting to increased cell proliferation, migration and polarity, that potentially contribute to development of the idiopathic pulmonary fibrosis [ 72 ].…”
Section: Hippo-yap Signaling In Lung Cellsmentioning
confidence: 99%